A Clinical Study to Compare Functional Outcome of Proximal HumerusFracture in Adults (18- 80yrs) Treated By Philos Platting andConservative Modalities - Divyesh Pragajibhai Jetpariya; Baiju Mukeshbhai Patel; Parth Pravinbhai Patel; Harsh Girishbhai Patel (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2022)
Introduction: It is the commonest fracture affecting the shoulder girdle in adults. Proximal humeralfractures account for almost 7% of all fractures and make up 80% of all humeral fractures. Thepurpose of this study is to carry out to enlighten functional outcome fracture proximal humerustreated with conservative and PHILOS platting and comparison of that. Material and Method:Twenty-six patients attended the Department Of Orthopaedics from May 2018 to August 2020 andwere involved in this study prospectively, out of which 11 were male, and 15 were female. Theywere analysed clinically and radiologically using Constant and Murley shoulder scoring criteria. Outof 26 cases, 12 were treated conservatively, and 14 were treated by Pen reduction internal fixation(ORIF) Result: Out of 12 patients treated conservatively, three had excellent, seven had good, and2 had fair functional outcome, whereas 14 patients treated by open reduction and internal fixationtwo had excellent, 4 had good, four had fair, and 4 had the poor functional outcome. Complicationswere seen in 9 patients. Out of that, five patients had shoulder stiffness, 3 had malunion, and 1 hadimpingement of implant. Conclusion: Proximal humerus fracture occurred most commonly in the4th to 6th decade of life. For minimally displaced fracture, treatment of choice is nonoperative. For 2part fracture treated with conservative modalities showed slightly better results than operatedpatients, but for 3 part fracture operated patients had somewhat better results than conservative.